THE TEACHER PROFESSIONAL COMPETENCE IN IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM IN CLASS 1 OF MADRASAH IBTIDAIYAH AL-FALAH LIMBOTO BARAT: TEACHER PROFESSIONAL COMPETENCE - Ali, Riskia Anggun Sari D.; Munirah, Munirah; Talango, Sitti Rahmawati (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
A professional teacher does not only provide learning to students by relying on books or guidelines for learning topics in the curriculum. Teachers must be able to provide inspiration as an example to students so that students are able to be creative, innovative and creative in learning as is the aim of the independent learning curriculum. This research aims to find out how the stages of learning are implemented, to find out what the professional competence of teachers is, and to find out the obstacles faced in implementing the independent curriculum in class 1 of MI Al-falah West Limboto. The research method used is descriptive qualitative. The focus of this research is the 1st grade teacher at MI AL-Falah Limboto Barat. The data collection technique uses interviews, observation and documentation. The data analysis technique uses data reduction, data presentation and conclusions. The results of this research show that a teacher can be said to be professionally competent, because he is in accordance with Indonesian Ministry standards no. 14 of 2005 regarding professional competence, namely by providing the best learning to students using an independent curriculum.